Perbandingan Metode Artificial Neural Network (ANN) dan Classification And Regression Tree (CART) Dalam Menentukan Penerima Bantuan Program Keluarga Harapan (PKH) - Septasari, Dita; Abdul Aziz, RZ. (Institut Teknologi Garut, 2024)
Poverty in Indonesia is influenced by several factors. In this case, the government is implementing various programs to improve the welfare of the community. One of these programs is the Family Hope Assistance Program (PKH). Predictions regarding PKH assistance recipients use the Artificial Neural Network (ANN) and Classification and Regression Tree (CART) methods to assist in the process of determining recipients of the family hope program. The Artificial Neural Network (ANN) and Classification and Regression Tree (CART) methods produce performance measurements (accuracy, precision, recall, and f1-score) from the data of Family Hope Assistance Program (PKH) recipients. The results of this study show that the Artificial Neural Network (ANN) method performs better than the Classification and Regression Tree (CART) method in predicting PKH recipients in Pringsewu Regency.